Biofuels in Malaysia: An analysis of the legal and institutional framework - Chin, M. (Center for International Forestry Research, 2011)
Malaysia is the world’s largest exporter and the second largest producer of crude palm oil. The government has sought to promote the production of biodiesel derived from palm-oil to capitalise on the growing international demand for biofuels, seen as an alternative to fossil fuels amidst concerns over rising fuel costs, greenhouse gas emissions and energy security. The Malaysian government launched its National Biofuel Policy in 2006 to promote the commercialisation, use, export and research of biodiesel derived from palm oil. Since then, soaring palm oil prices coupled with a decline in fossil fuel prices have significantly reduced the economic viability of palm oil– based biodiesel production in the country. Consequently, biodiesel production is suppressed to about 10% or less of the total domestic installed capacity. In February 2010, the government decided to delay implementation of the mandate on the sale of B5 biodiesel blend until June 2011. The B5 mandate applies only to the Central Region of Peninsular Malaysia and it is unlikely that the domestic demand generated will be sufficient to sustain the industry. The current outlook for the Malaysian biodiesel industry looks rather uncertain, as no substantial government subsidies appear to be forthcoming in the near future. Furthermore, the industry is extremely vulnerable to fluctuating palm oil and petroleum prices and the development of restrictive biofuel policies in key consumer markets. This paper provides an overview of the development of the Malaysian biodiesel industry and a brief assessment of the effectiveness of national policies, strategies and laws that promote and regulate the industry.